Analisis Dalam Menentukan Pemilihan Produk Handphone Menggunakan Metode Analytical Hierarchy Process (AHP) - Rizki Pratama; Sundari Retno Andani; Jalalludin Jalalludin (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Handpone/smartphone is one of the most popular electronics by melenial people at this time, various handphone/smartphone products have also been lauched and varios types, so it makes the developers confused to choose whitch handpone/smartphone is the best among the good, starting From the price, comfout and durability, I analyse several mobile phones that I think are comfortable, affordable, and have specifications that are increasingly increasing, here are some brands of handpone/smartphone that I analyzed, namely : 1. Samsung, 2. Oppo, 3. Xiaomi, of the thre, namely Xiaomi, I analyzed using the Analytical hierarchy Process (AHP) method, which resulted in a single winner for the selection of the best handpone/smartphone among the bes